Editorial Bodies : Perfection and Rejection in Ancient Rhetoric and Poetics - Kennerly, Michele (Book collections on Project MUSE., 2018)
A study that reveals the emergence and endurance of vocabularies, habits, and preferences that sustained ancient textual cultures.